Accuracy of lead risk assessment questionnaire in predicting elevated blood lead levels in children - Sadasivam, Kanimozhi; Chinnasami, Balaji; Hariharan, Apurva; Ramraj, Balaji; Saravanan, Rahul; Ayyavoo, Saravanan (International Journal of Contemporary Pediatrics, 2019)
Background: Lead toxicity in children is a serious problem affecting their neurodevelopment. Although CDC mandates screening for lead toxicity regularly in children, India doesn’t have any lead related public health program in place. In resource limited India a prescreening lead risk assessment questionnaire will be more economical than universal screening for blood lead levels (BLL). Authors aim to evaluate the accuracy of a validated modified CDC lead risk assessment questionnaire in predicting elevated BLL. Methods: Authors conducted an explorative cross-sectional study from July to August 2017 in 340 children aged 6 months to 6 years. A standardized self-administered questionnaire modified from CDC lead risk assessment questionnaire was administered in the children. Also, BLL were measured in all study subjects using lead care II analyser. Data from questionnaire were compared with BLL to test the accuracy of questionnaire. Results: Blood lead levels was high (>5ug/dl) in 57.9% of study subjects especially in children between 24-35 months. Employment in battery manufacturing companies (P=0.0001), usage of cosmetics (P=0.019), parental smoking history (P=0.001), involvement in painting, arts (P=0.0001) and malnourished children (P=0.018) were the risk factors associated with undesirable BLL. The modified questionnaire had a sensitivity of 87.9% and specificity of 66.7% for detecting elevated BLL. Conclusions: The modified CDC lead risk assessment questionnaire is a sensitive tool in identifying high risk cases of lead toxicity in children.